Anticancer (liver cancer cell lines) and antioxidant activity of Cassia auriculata flower extract from acetone and methanol solvents - Padmalochana, K (Journal of Drug Delivery and Therapeutics, 2018)
This research paper was communicated to elucidate the antioxidant and anticancer activities of acetone and methanol extract of Cassia auriculata flower. Antioxidant activity was assessed against DPPH and hydroxyl free radical. The anticancer activity was examined by inhibition on liver cancer cell lines. The highest antioxidant activity was found for methanol extract (IC50: 46.28 μg/ml) than acetone extract (IC50: 52.60 μg/ml) on DPPH free radical. The IC50 values for methanol and acetone extract was found to be 47.05 and 56.01±1.85 µg/ml, respectively on hydroxyl radical. The highest anticancer activity was found for methanol extract to be 36.10±2.46 µg/ml. Among these extract methanol extract have high antioxidant and anticancer activity. Keywords: Antioxidant, anticancer, Plant